Development and Usability Evaluation of an IT-Based Disaster Medical Record System in South Kalimantan, Indonesia - Hastin Atas Asih; Indrayadi Indrayadi; Muhamad Heriyadi; Nur Sa'adah Hayati; Rahardina Dwi Chantika (Pancasakti Journal Of Public Health Science And Research, 2025)
Indonesia, as a disaster-prone region, requires a resilient health information system. Conventional paper-based medical records are vulnerable to damage and inefficient in emergency response, making the development of an electronic disaster medical record crucial. This study aims to design and test the usability of a web-based electronic disaster medical record prototype. This study used a prototyping method involving 32 medical records staff from hospitals in South Kalimantan. System usability evaluation was conducted using the System Usability Scale (SUS) questionnaire through usability testing with a disaster documentation task scenario. Statistical analysis was performed by calculating the SUS score using a standard formula that yields a score of 0-100. The results showed an average SUS score of 79.31, which is classified as grade B (good) on the acceptability scale, indicating that the system is acceptable and meets basic usability aspects well. This finding proves that the electronic disaster medical record prototype is feasible and has the potential to improve victim data management, although there is still room for refinement of certain elements to achieve an excellence level. The implementation of this system is expected to be integrated with the national health platform to support more effective disaster response.